The questionable ethics of civil forfeiture - Dick M. Carpenter (Freedom from Fear, 2018)
On a cool, sunny November day, Mark Brewer - a disabled decorated U.S. Air Force veteran - was driving through the state of Nebraska on his way to Los Angles to visit his uncle. While there, Brewer planned to make a down payment on a house. To that end, he was carrying more than 60,000 in cash, that he had saved during his military service and from disability payments.